1987
DOI: 10.1073/pnas.84.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Differential mRNA transcription during salinity stress in barley

Abstract: The molecular and genetic bases of salinity tolerance in plants are not understood. Gene expression at the mRNA level was investigated in a salt-tolerant and a saltsensitive genotype of barley. Seedlings were exposed to NaCl stress and translatable mRNAs were isolated from root and shoot tissues. A reticulocyte cell-free system was programed with barley mRNAs and the in vitro products were resolved on two-dimensional polyacrylamide gels following isoelectric focusing or nonequilibrium pH gradient gel electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 18 publications
1
30
2
Order By: Relevance
“…Several other groups are involved in similar work (8,9,19,22) using a slightly different approach in so far as they study gene expression in either salt adapted lines of glycophytes or the differences in gene expression between salt tolerant and sensitive genetic variants. One important character by which salt sensitive plants differ from halophytes as well as from the selected cell culture lines and salt tolerant cultivars is that glycophytes respond to salt stress by arrest of growth.…”
Section: Resultsmentioning
confidence: 99%
“…Several other groups are involved in similar work (8,9,19,22) using a slightly different approach in so far as they study gene expression in either salt adapted lines of glycophytes or the differences in gene expression between salt tolerant and sensitive genetic variants. One important character by which salt sensitive plants differ from halophytes as well as from the selected cell culture lines and salt tolerant cultivars is that glycophytes respond to salt stress by arrest of growth.…”
Section: Resultsmentioning
confidence: 99%
“…Hurkman et al (1994) and Hurkman and Tanaka (1996) were the 1st to report GLP induction in barley roots during salt stress. Earlier, Ramagopal (1987) in barley and Naqvi et al (2009) in rice observed the induction of apparently similar proteins during salt stress by two-dimensional electrophoresis, although they did not characterize these proteins by sequencing. It has also been reported that salt stress can enhance wheat germin promoter activity in transgenic tobacco Bernier, 1997, 1999).…”
Section: Effect Of Dehydration and Salt Stress On Osrglp2 Promoter Acmentioning
confidence: 99%
“…The association between osmotin accumulation and stable NaCI tolerance indicates that cells with a stable genetic change affecting the accumulation of osmotin are selected during prolonged exposure to high levels of NaCI. This stable alteration in gene expression probably affects salt tolerance.NaCl stress evokes changes in the levels of several plant gene products (8,12,14,21,(24)(25)(26)(27)(28). Since none of these gene products have been shown to be unequivocally involved in physiological adaptation to NaCl stress, additional information on the regulation of their expression is needed (11).…”
mentioning
confidence: 99%